Corporate Social Responsibility and Brand Loyalty: The Mediating Role of Brand Experience and Brand Trust among students in Nepali Business Schools - Pokhrel, Laxman; Bajracharya, Samyak; Subedi, Gopal (Journal of Business and Management, 2024)
Background: Corporate social responsibility (CSR) is crucial in business schools as it instills ethical values and commitment to societal welfare, fostering a positive brand experience (BE), and brand trust (BT) among stakeholders to bring out a feeling of brand loyalty (BL) among them. Despite the need for contextual understanding of CSR in Nepali business schools, there is a paucity of literature on CSR in Nepali business schools.Objectives: The paper aims to explore role of BE and BT as mediator in connection between CSR and BL among students at Nepali business schools.Methods: Purposive sampling was used in this study’s cross-sectional survey research design to gather data from 256 students. To test hypotheses, the partial least squares structural equation modeling (PLS-SEM) was employed.Results: The findings indicate that BE act as a mediator between CSR and BL among Nepali business school students, while BT doesn’t have a mediating effect. Furthermore, CSR initiatives positively influence BE and BT, leading to increased BL. Nevertheless, the impact of BT on BL was found to be insignificant.Conclusion: The findings of the study could offer significant value for business schools and prepare CSR policies to develop loyal relationships with students.